PERAN PERUSAHAAN UMUM BADAN URUSAN LOGISTIK DALAM MENJAGA KETERSEDIAAN PANGAN BERAS DAN STABILISASI HARGA BERAS DI KANTOR CABANG KABUPATEN OGAN KOMERING ULU - Shela Angelina; Rakhmat Saleh; Eva Susanti (Jurnal Riset Multidisiplin Edukasi, 2026)
Rice is a basic necessity for society, the fulfillment of which is guaranteed by the 1945 Constitution of the Republic of Indonesia. The state is responsible for ensuring food availability, accessibility, and affordability for all citizens. However, in practice, various challenges remain, such as fluctuations in rice prices and supply, particularly ahead of National Religious Holidays and during periods of scarcity, including in Ogan Komering Ulu Regency. Perum Bulog, as a State-Owned Enterprise assigned by the government under Presidential Regulation Number 48 of 2016, plays a strategic role in maintaining price stabilization and rice availability. This study aims to examine the role of Perum Bulog in maintaining rice availability and price stabilization in Ogan Komering Ulu Regency. The research employed a qualitative descriptive method with data collection techniques including interviews, observations, and documentation. The study was conducted from June 24 to July 20, 2025.The results indicate that Perum Bulog Ogan Komering Ulu Branch has carried out its role effectively through the purchase of farmers’ unhusked rice in accordance with the Government Purchase Price (HPP), the distribution of rice through the Food Supply and Price Stabilization Program (SPHP), and the management of Government Food Reserves (CPP) for Beneficiary Families. Despite an increase in distribution, rice stocks remained stable.The study concludes that the role of Perum Bulog has supported the principles of food security, namely availability, accessibility, and stability. Therefore, it is recommended that Bulog continue to strengthen paddy absorption, enhance cross-sectoral coordination, and maintain the stability of regional food stocks.